Encouraging Anti-Racism Education Policy from Conflict Perspective - Sukardi Sukardi; Sajida Sajida (Journal of Transformative Governance and Social Justice, 2023)
Since discrimination and labeling of ethnic Chinese are still embedded in society. The goal of this paper is to encourage different policies that try to solve racial conflicts, especially through education as a preventive measure to raise a generation with a lot of knowledge and a lot of patience. This paper reviews various alternative efforts to eliminate the issue of racism among ethnic Chinese. This review finds that reconciliation can be achieved through education and other methods. It is also demonstrates that efforts have been made by the government to initiate anti-racism education as part of the conflict resolution process. Nevertheless, this implementation is a long way from being adequate or successful. There are still many records that need to be corrected and evaluated by the government to encourage anti-racism education policies.